ON A CLASS OF MATRIX DIFFERENTIAL EQUATIONS WHOSE GENERAL SOLUTION IS POLYNOMIAL - Piperevski, Boro M. (Matematichki Bilten, 2008)
In this article a class of matrix differential equations we observe. The necessary and sufficient conditions, under which this class has a general polynomial solution, are obtained. The formula of that general polynomial solution is also obtained.